Blood pressure control and its associated factors among hypertensive patients at health clinics in Kuala Muda district, Kedah - Norwati, Daud; Teoh, Soo Huat (2016)
Introduction: Primary care providers play a major role in treating patients with hypertension. Despite the wide availability of primary healthcare facilities, blood pressure control remains poor. This study aimed to determine the proportion of blood pressure (BP) control and its associated factors among patients attending health clinics in Kuala Muda district, Kedah. Methods: A retrospective study was done from April to May 2015 at seven health clinics in Kuala Muda district, Kedah. Stratified random sampling was used and data from patients’ record were retrieved using self-designed data collection proforma. Samples chosen were those newly diagnosed hypertension patients from January 2014 onwards, aged more than 18 years old and with at least 6 months follow up. Controlled blood pressure was defined as in the Malaysian Clinical Practice Guidelines for the Management of Hypertension (4th edition). Results: A total of 331 hypertensive patient records were selected. There were 160 patients (48.3%) with controlled BP. Multiple logistic regression analysis showed that age (OR= 1.03, 95% CI: 1.01, 1.05, p= 0.041) and systolic BP at presentation (OR= 0.95, 95% CI: 0.93, 0.96, p< 0.001) were associated with controlled BP. Initial BP stage and risk level at presentation were not associated with controlled BP. Conclusion: BP control in this population was at par with other studies. However, with the increasing prevalence of hypertension and its complications, multiple strategies should be implemented to increase the proportion of patients with controlled blood pressure.